Pinkalicious at the fair - Kann, Victoria (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
When she and Molly go to the fair, Pinkalicious wishes her unicorn could enjoy the fair with them.
Ages 4-8.
Guided reading level I.
Accelerated Reader
aj03/19.
Keywords: Pinkalicious -- (Fictitious character) -- Juvenile fiction; Fairs -- Juvenile fiction; Friendship -- Juvenile fiction; Unicorns -- Juvenile fiction